Analysis of Product Quality and Service Quality on Customer Satisfaction at the Surya Mart Mart Business Center using the Structural Equation Modeling Method - Yannu Prasetyo; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2021)
Service quality is a superior value for customers to improve business performance or company marketing represents a level of excellence to meet consumer expectations. Therefore, it is not necessary to know what factors affect product quality and service quality at the Surya Mart Business Center Surya Mart Business Center. Surya Mart Business Center Surya Mart's Business Center is located on campus 2 of the Muhammadiyah University of Sidoarjo (UMSIDA), the market is for students, lecturers, UMSIDA employees and the surrounding community. To find out the factors that affect product quality and service quality, research uses Structural Equation Modeling, which is ia statistical technique that is able to analyze the pattern of relationships between data constructs and indicators, one data construct and another, and direct measurement errors. The results showed that the highest loading factor value was 1.329 in the discount indicator, for the term indicator, namely the additional factor with a value of 0.664. Test structural modeling on the relationship between constructs that have a casual or causal relationship. The results of this study, Variable Product Quality and Service Quality, the second variable has a significant influence on the Customer Satisfaction variable.